Political Cycles, Political Institutions and Public Expenditure in India, 1980-2000 - Sáez, Lawrence; Sinha, Aseema (British Journal of Political Science, 2009)
In Western democracies it is held that parties and their positions affect how politicians choose to make public expenditure and investment. This article examines the public policy choices of politicians in India, a large well-established democracy with remarkable subnational variation. Public expenditure, from education and health to agriculture and irrigation, is analysed. Counterintuitive findings - that election timing and political factors play a strong role in the subnational states, and that party competition increases investment in education - are explained by highlighting the role economic and political uncertainty plays in politicians' choices. Building a 'Polanyi' argument enhanced by a supply-side mechanism highlights the importance of compensation and insurance and the imperatives of political stability for subnational politicians, who attempt to maximize re-election chances in an uncertain environment.
Keywords: India; budget - law and legislation; elections; government purchasing; government spending policy; policy sciences; public administration; public spending; representative government; tax and expenditure limitations